Guidelines for treatment of atopic dermatitis - Suzana Ljubojević Hadžavdić; Nives Pustišek; Liborija Lugović Mihić; Suzana Ožanić Bulić; Neira Puizina-Ivić; Sandra Peternel; Melita Vukšić Polić; Sandra Marinović Kulišić; Ružica Jurakić Tončić; Slobodna Murat-Sušić; Karmela Husar; Mihael Skerlev; et al. (Liječnički vjesnik, 2022)
Atopic dermatitis is a common, chronically recurrent inflammatory skin disease characterized by a complex etiopathogenesis and a variable clinical phenotype. The clinical presentation is heterogeneous, and the disease is characterized by a recurrent dermatitis, intense itching and a significant impact on the quality of life of patients and their family. The diagnosis is based on the clinical presentation according to the standardized diagnostic criteria, while the assessment of disease severity of the disease is based on the standardized tools for disease severity assessment. Treatment should be tailored to each patient profile, and the goal of the treatment is focused on decreasing symptoms and renewing damaged skin barrier, preventing the exacerbation of the disease and preventing or treating the complications and comorbidities, and decreasing the negative influence of the disease on the patient’s quality of life. Due to progress in understanding the etiopathogenesis, treatment options have significantly expanded in the past years. The Croatian Society of Dermatovenerology of the Croatian Medical Association is presenting guidelines for diagnosis and treatment of atopic dermatitis. These guidelines are the result of consensus of Croatian experts based on critical analysis of relevant, evidence-based scientific literature.